Effects of Compound Enzymes in Nursery Pig Diets of Different Nutrient Density - Ty H. Kim; Jamil E. G. Faccin; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Chad B. Paulk; Ying Zhou; Xuerong Song; Xiuyi Wu; Franco S. Matias-Ferreyra; Raghavendra G. Amachawadi; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 355 nursery pigs (DNA 241 × 600, initially 29.3 ± 0.52 lb BW) were used in a 35-d growth study to determine the effects of compound enzymes (Sunzyme; Wuhan Sunhy Biology Co., Ltd., Wuhan, P.R. China) on growth performance, intestinal morphology, and nutrient digestibility in nursery pigs fed diets of different nutrient density. At approximately 19 d of age, pigs were weaned, randomly allotted to pens, and fed common phase 1 and 2 diets. On d 24 post-weaning, considered d 0 of the study, pigs were blocked by average pen BW and allotted to one of six dietary treatments in a randomized complete block design with four or five pigs per pen and 12 pens per treatment. Treatment diets were formulated in two dietary phases and fed from d 0 to 22 and d 22 to 35, respectively. The six treatments included two corn-soybean meal-based diets (Corn-SBM; CS) with either 0 (CS + 0) or 0.01% (CS + 0.01) enzyme and four corn-soybean meal-wheat middling-low oil DDGS-based diets (Corn-SBM-By-product; CSBP) with lower dietary energy/CP with 0 (CSBP + 0), 0.01 (CSBP + 0.01), 0.02 (CSBP + 0.02), or 0.03% (CSBP + 0.03) enzyme. At the conclusion of the study, fecal samples were collected from six pigs per treatment to determine ATTD of DM, CP, ADF, and NDF. The same pigs were then euthanized, and ileal digesta and tissue samples were collected to determine AID of AA and small intestine morphology. Overall, pigs fed CS diets had increased (P < 0.05) ADG and improved (P < 0.05) F/G compared to pigs fed CSBP diets, but there were no treatment effects (P > 0.05) on ADFI. Pigs fed CSBP diets had increased (P < 0.05) duodenal villus height compared to pigs fed CS diets, but added enzyme decreased (P < 0.05) the duodenal villus height in CS diets and decreased (linear, P < 0.05) duodenal villus height and VH:CD in CSBP diets. There were no effects (P > 0.05) on jejunal or ileal morphology. Pigs fed CS diets had increased (P < 0.05) ATTD of DM, CP, and ADF, AID of Arg, Asp, and Trp compared to pigs fed CSBP diets. There was a quadratic reduction (P = 0.015) in AID of Met as enzyme increased in CSBP diets. In summary, pigs fed CS diets had improved growth performance, ATTD of DM, CP, and ADF, and AID of Arg, Asp, and Trp compared to pigs fed CSBP diets. The addition of a compound enzyme had no effect on overall growth performance but had a negative impact on duodenal morphology, ATTD of DM and CP, and AID of Met in CSBP diets.
Keywords: carbohydrase; digestibility; growth; nursery pigs; protease